Value of Renal Histology in Predicting Cardiorenal Outcomes in Heart Transplant–listed Patients. Issue 1 (16th December 2022) - Barua, Sumita; Yang, Tao; Conte, Sean; Bragg, Christopher; Sevastos, Jacob; Macdonald, Peter S.; Muthiah, Kavitha; Hayward, Christopher S.
Abstract : Background: Cardiorenal syndrome (CRS) contributes significantly to morbidity and mortality in patients requiring mechanical circulatory support and transplantation. There are no validated markers to predict major adverse kidney events (MAKEs), for which simultaneous heart-kidney transplant (SHKT) could offer improved survival. We evaluate renal histology in predicting MAKEs in transplant-listed patients. Methods: We identified 18 patients with renal histology consistent with CRS from 655 consecutive heart transplant-listed patients between 2010 and 2019. Biopsies were analyzed for glomerular, tubular, interstitial, and arteriolar changes tallied to give a biopsy chronicity score. The primary outcome, MAKE, was a composite of death, need for renal replacement therapy (RRT), or estimated glomerular filtration rate decline >50%. These were evaluated at 2 time points: before and following the transplant. Secondary outcomes included the individual components of the composite outcomes and the need for short-term RRT following the transplant. Results: The mean age was 52.3 y, 22% were female. Five patients did not survive to transplant. One patient underwent successful SHKT. MAKE occurred in 8 of 18 before the transplant and in 8 of 13 following the transplant. Neither outcome was predicted by baseline biochemistry. The biopsy chronicity score was significantly higher in patients with MAKE before transplant (4.3 versus 1.7, P = 0.024) and numerically higher in patients requiring short-term RRT following transplant (3.2 versus 0.7, P = 0.075). Contrary to limited previous literature, interstitial fibrosis did not predict any outcome, whereas tubular atrophy and arteriosclerosis were associated with MAKE before transplant. Conclusions: A higher biopsy chronicity score was associated with adverse kidney endpoints, raising its potential utility over standard biochemistry in considering SHKT referral.